2017
DOI: 10.1002/jcb.26453
|View full text |Cite
|
Sign up to set email alerts
|

c‐Abl tyrosine kinase regulates neutrophil crawling behavior under fluid shear stress via Rac/PAK/LIMK/cofilin signaling axis

Abstract: The excessive recruitment and improper activation of polymorphonuclear neutrophils (PMNs) often induces serious injury of host tissues, leading to inflammatory disorders. Therefore, to understand the molecular mechanism on neutrophil recruitment possesses essential pathological and physiological importance. In this study, we found that physiological shear stress induces c-Abl kinase activation in neutrophils, and c-Abl kinase inhibitor impaired neutrophil crawling behavior on ICAM-1. We further identified Vav1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Several kinases from different families, including focal adhesion kinase (FAK) and c-Src, mediate the signal transduction of integrins (22). c-Abl has been shown to be colocalized with integrin α5 and activated in cells subjected to fibronectin treatment (23) or fluid shear stress (24). Furthermore, with the emerging importance of NRTKs in neurodegenerative diseases, chronic myeloid leukemia, and carcinogenesis, tyrosine kinase inhibitors are being used in the clinic (21).…”
Section: Introductionmentioning
confidence: 99%
“…Several kinases from different families, including focal adhesion kinase (FAK) and c-Src, mediate the signal transduction of integrins (22). c-Abl has been shown to be colocalized with integrin α5 and activated in cells subjected to fibronectin treatment (23) or fluid shear stress (24). Furthermore, with the emerging importance of NRTKs in neurodegenerative diseases, chronic myeloid leukemia, and carcinogenesis, tyrosine kinase inhibitors are being used in the clinic (21).…”
Section: Introductionmentioning
confidence: 99%
“…Because Rac1/Cdc42 phosphorylation is a negative indicator of Rac1/Cdc42 GTPase activation, MT likely causes activation of Rac1/Cdc42 GTPase in MKs (Figure D,E). This activation is supported by a decrease in PAK, LIMK, and cofilin phosphorylation (Figure F‐J), as cofilin phosphorylation is mediated by Rac1/Cdc42 effector PAK, via the activation of the downstream effector LIMK . Interestingly, we found that the Rac1/Cdc42 GTPase inhibitors, especially the Rac inhibitor EHop‐016, significantly blocked the activation induced by MT, which was revealed by a more prominent Rac1/Cdc42 phosphorylation after pretreatment with EHop‐016 compared with that after pretreatment with the Cdc42 inhibitor ZCL278.…”
Section: Resultsmentioning
confidence: 62%
“…This activation is supported by a decrease in PAK, LIMK, and cofilin phosphorylation ( Figure 4F-J), as cofilin phosphorylation is mediated by Rac1/Cdc42 effector PAK, via the activation of the downstream effector LIMK. 19,20 Interestingly, we found that the Rac1/Cdc42 GTPase inhibitors, especially the Rac inhibitor EHop-016, significantly blocked the activation induced by MT, which was revealed by a more prominent Rac1/Cdc42 phosphorylation after pretreatment with EHop-016 compared with that after pretreatment with the Cdc42 inhibitor ZCL278. Therefore, the activation of Rac1/Cdc42 GTPase is mainly mediated by Rac GTPase (Figure 4J,K).…”
Section: Gtpase Are Activated During Mt-facilitated Thrombopoiesismentioning
confidence: 80%
“…However, whether this symptom improvement was completely attributed to SR7826/LIMKi3-induced detrusor relaxation may not be concluded from our data. OAB symptoms may also be associated with inflammation in the bladder, while LIMK has been indicated as a regulator during inflammatory processes in some other diseases 54 , 55 . However, any additional effect of LIMK on the inflammation associated OAB remains unclear, and needs further exploration.…”
Section: Discussionmentioning
confidence: 99%